Mental Health Stigma and Wellbeing Among Commercial Construction Workers: A Mixed Methods Study. Issue 8 (August 2020) - Eyllon, Mara; Vallas, Steven P.; Dennerlein, Jack T.; Garverich, Suzanne; Weinstein, Daniel; Owens, Kathleen; Lincoln, Alisa K.
Abstract : Objective: The aim of this study was to understand the relationship between mental health stigma and wellbeing in a sample of commercial construction workers. Methods: A sequential quantitative to qualitative mixed methods study was conducted. First, 264 workers were surveyed and logistic regression examined the associations between mental health stigma and psychological distress, substance abuse, and sleep; then, data from eight key informant interviews and six focus groups with workers were analyzed thematically. Results: Stigma was significantly associated with psychological distress and impaired sleep, but not with substance abuse. Key informants and workers discussed the prominence of stigma on worksites and how the masculine culture of the industry and job insecurity contributed to stigma. Conclusion: Stigma poses a barrier to addressing mental health among workers; peer support and improved human resources may be promising. Abstract : Supplemental Digital Content is available in the text